Correlation between Allergic Rhinitis and History of Infantile Atopic Dermatitis - Mutiara Arikah Balqis; Hikmah, Zahrah; Indramaya, Diah Mira; Damayanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Atopic march is one of the global health problems that is commonly found in children. The prevalence of allergic rhinitis in Indonesia reaches to 1.5% to 12.4% and continues to increase every year. Allergic reactions can affect all tissues and organs in the body. Some clinical manifestations of allergies are allergic rhinitis, atopic dermatitis, and asthma (atopic march). Atopic march often begins in infancy with the development of atopic dermatitis later in life. Purpose: To analyze the correlation between the prevalence of allergic rhinitis and history of infantile atopic dermatitis in children. Methods: This research used an observational analytic design with a cross-sectional approach. Result: The data were categorized based on a history of atopic dermatitis and the diagnosis of allergic rhinitis. The statistical tests revealed a relationship between the incidence of allergic rhinitis and history of infantile AD in children. The chi-square test yielded a p-value of 0.014 and a contingency coefficient value of 0.213. The odd ratio (OR) value at a confidence level (CL) of 95% and a limit of 1.312 – 6.256 is 2.865, which means that patients who have a history of AD have a 2.8 times higher risk of experiencing AR. Conclusion: The conclusion of this study is that there is a correlation between the incidence of allergic rhinitis and history of infantile atopic dermatitis.